"Just a natural move towards English": Gulf youth attitudes towards Arabic and English literacy. Issue 1 (1st June 2014) - O'Neill, Gary T.
Abstract : This paper reports a sub-set of results from a mixed-method ethnographic study of literacy among female graduates and undergraduates of a United Arab Emirates public university. With reference to survey data and two in-depth interviews, the paper focuses in particular on the predispositions and preferences of these women with regard to reading and writing in English and Modern Standard Arabic. Employing a New Literacy Studies theoretical framework along with a number of concepts developed by Bourdieu, the paper finds that literacy practices in this context are developing rapidly, influenced by the diverse transnational linguistic marketplaces in which these women grow up. Suggestions are made with regard to possible directions for curricular development in higher education in this region based on the opinions expressed by these young women.